HUBUNGAN ANTARA MOTIVASI BELAJAR DENGAN HASIL BELAJAR IPA SISWA KELAS VIII SMPN 1 KARANG PENANG SAMPANG - Faizah, Nurul; Hadi, Wiwin Puspita; Tamam, Badrud; Qomaria, Nur; Yasir, Mochammad (Program Studi Pendidikan IPA, Universitas Trunojoyo Madura, 2023)
This study aims to determine the feasibility and student responses to the relationship between learning motivation and student learning outcomes in grade VII SMPN 1 Karang Penang Sampang. This research is an ex-post facto research with a quantitative approach. The subjects of this study were all students of class VIII SMPN 1 Karang Penang with a total of 31 students. The results of this study indicate that there is a relationship between students' learning motivation and student learning outcomes in Natural Science subjects in the even semester of the 2021/2022 academic year with a significance value of 0.002 less than 0.05 and a calculated F of 0.535% with a fairly valid category. know that there is a relationship between motivation and student learning outcomes.